Islamic Corporate Social Responsibility (ICSR): Kerangka Konseptual dan Pelaporan Berdasarkan Maqashid Syariah - Salimudin, Mumud; Jubaedah, Dedah (Jurnal Ilmiah Ekonomi Islam, 2024)
This article aims to explore Islamic Corporate Social Responsibility (ICSR) in terms of conceptual framework and social reporting based on Maqashid Sharia. The research uses a qualitative approach with the type of literature study. In Islam, the concept of social responsibility has a strong foundation through the teachings of the Qur'an and Hadith, which promote justice, balance, and concern for others. Islamic Corporate Social Responsibility (ICSR) integrates these principles with modern CSR practices, thus creating a holistic approach and in line with Islamic values. The framework of Islamic Social Responsibility Based on Maqashid Sharia has a close relationship with the three concepts of social responsibility relations played by humans. The three relationships are man's relationship of responsibility with God, man's relationship of responsibility with man and man's relationship with the environment. The three relationships are based on five principles, namely tawhid, caliph, justice, ukhuwah, and problem creation. From the five principles of human social responsibility relations, four dimensions are formed, namely economic, legal, ethical, and philanthropic